Pengaruh Pengawasan Dan Budaya Kerja Terhadap Kinerja Pegawai Pada Unit Rektorat Universitas PGRI Palembang - Nisa' Ulul Mafra (Universitas PGRI Palembang, 2013)
The research was premised titles Influence of Controlling and Work Culture to Performance of Employee at Unit Rectorat PGRI University of Palembang.This study was conducted with the formulation of the problem how to influence controlling and work culture together and partially on employee at unit rectorat PGRI University of Palembang. The purpose of the study are: to identify and analyze the influence of employee at unit rectorat PGRI University of Palembang together and partially on employee at unit rectorat PGRI University of Palembang.Methods of study: this study research design that will be used is a multiple regression model, the design of the study that will reveal the collective effect of independent variables on the dependent variable. The data used are primary data and secondary data were collected through questionnaires. The instrument of this study using proportionate stratified random sampling technique, and a total sample of 155 employees at unit rectorat PGRI University of Palembang.Results: the performance of the employees at unit rectorat PGRI University of Palembang strongly influenced by controlling and work culture is proved by the analysis of the value of the coefficient of determination (R2). In this study, the coefficient of determination value of 0,415, which means the variables performance of employees of 41,5% can be explained jointly by the controlling (X1) and work culture (X2) while the remaining 58,5% is explained by factors or other variables were not examined in this study. Keywords: Controlling,Work Culture, Performance